The C(3P) + O2(3Σg−) → CO2 ↔ CO(1Σ+) + O(1D)/O(3P) reaction: thermal and vibrational relaxation rates from 15 K to 20 000 K. Issue 19 (5th May 2021) - San Vicente Veliz, Juan Carlos; Koner, Debasish; Schwilk, Max; Bemish, Raymond J.; Meuwly, Markus
Abstract : Reaction and vibrational relaxation rate computed for C( 3 P) + O2 ( 3 Σg − ) ↔ CO( 1 Σ + ) + O( 1 D)/O( 3 P) for a wide range of temperatures using quasiclassical trajectory calculations on five new potential energy surfaces for different electronic states. Abstract : Thermal rates for the C( 3 P) + O2 ( 3 Σg − ) ↔ CO( 1 Σ + )+ O( 1 D)/O( 3 P) reaction are investigated over a wide temperature range based on quasi classical trajectory (QCT) simulations on 3-dimensional, reactive potential energy surfaces (PESs) for the 1 A′, (2) 1 A′, 1 A′′, 3 A′ and 3 A′′ states. These five states are the energetically low-lying states of CO2 and their PESs are computed at the MRCISD+Q/aug-cc-pVTZ level of theory using a state-average CASSCF reference wave function. Analysis of the different electronic states for the CO2 → CO + O dissociation channel rationalizes the topography of this region of the PESs. The forward rates from QCT simulations match measurements between 15 K and 295 K whereas the equilibrium constant determined from the forward and reverse rates is consistent with that derived from statistical mechanics at high temperature. Vibrational relaxation, O + CO( ν = 1, 2) → O + CO( ν = 0), is found to involve both, non-reactive and reactive processes. The contact time required for vibrational relaxation to take place is τ ≥ 150 fs for non-reacting and τ ≥ 330 fs for reacting (oxygen atom exchange) trajectories and the two processes are shown to probe different parts of the global potential energy surface. In agreement with experiments, low collision energy reactions for the C( 3 P) + O2 ( 3 Σg −, ν = 0) → CO( 1 Σ + ) + O( 1 D) lead to CO( 1 Σ +, ν ′ = 17) with an onset at E c ∼ 0.15 eV, dominated by the 1 A′ surface with contributions from the 3 A′ surface. Finally, the barrier for the COA ( 1 Σ + ) + OB ( 3 P) → COB ( 1 Σ + ) + OA ( 3 P) atom exchange reaction on the 3 A′ PES yields a barrier of ∼7 kcal mol −1 (0.300 eV), consistent with an experimentally reported value of 6.9 kcal mol −1 (0.299 eV).